Determinants of People’s Participation in Forest Protection and Management: A Study in Kaski, Nepal - Ranjit, Yogesh (Economic Journal of Development Issues, 2016)
Forests are easily available renewable natural resources in the world that directly and indirectly provide socio-economic benefits to the people living in and around the forests and also environmental protection and ecological balance to the global people. In Nepal, traditionally people’s participation in forest protection and sustainable management was very popular through many informal traditional and indigenous forest management committees. But, unfortunately, there was a huge lost of forests in quantity, quality and density due to some unfavorable socio-economic and political situations. So, the government has formally, legally and gradually shifted from centralized to decentralized protection and management of forests since mid of 1970’s through various forest plans, policies, acts, regulation and guidelines. The major aims of people’s participation are to get basic forest products, socio-economic development, and overall improvement of forest resources. Moreover, the role of I/NGOs and other stakeholders should be as partner, advisor, facilitator and more technical supporter for effective participation of people. However, the major challenges of people’s participation is how to make meaningful involvement of local people in better forest protection, management and sustainable development so that they will get sustainable economic benefits for livelihood, environmental protection and ecological balance.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue; Page: 175-186